PERANCANGAN VIDEO PROFILE SEKOLAH EKKLESIA DENGAN MENGGUNAKAN LINEAR STRATEGY UNTUK MEMBANGUN CITRA POSITIF SEKOLAH - Setyawan, Martin; Cristo, Jonathan Laskar; Wenas, Michael Bezaleel (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2024)
Ekklesia School is a holistic school that prioritizes the personal development of its students. The limited information about Ekklesia School, including its teaching system, facilities, and the quality of its teachers, has resulted in a low level of awareness about the school, This has resulted in a lack of students enrolling in the school. Therefore, there is a need for informational media that can summarize information about Ekklesia School through audiovisual media, such as a video profile. Research in the form of a video profile with a clear message and information, supported by strong visuals and narration, can help the audience understand the message conveyed in the video profile. This research applies qualitative methods and a linear strategy in its design process, enabling the delivery of current and in-depth information and messages about Ekklesia School